Students' Concept Understanding in Solving Mathematical Literacy Problems on The Material of Linear Equations of Two Variables - Habibatunnurrohmah Aisyah; Purwanto Purwanto; Chandra Tjang Daniel (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study aims to describe how well students understand concepts when working with linear equations with two variables in math literacy assignments. The study design uses descriptive qualitative approach. The study subjects were two eighth-grade students based on three categories of conceptual understanding determined during the data reduction procedure to become study participants taken at SMP Negeri 1 Lamongan. The data collection involves providing mathematical literacy exercises on linear equation of two variables (SPLDV) and conducting interviews. Students with medium understanding could grasp basic concepts but struggled with reasoning and complete representations, while those with low understanding relied on memorization and failed to translate real-world problems into mathematics, indicating a strong link between conceptual depth and mathematical literacy performance.